Hubungan Asupan Natrium Dan Kalium Terhadap Tekanan Darah Pada Pegawai Negeri Sipil (PNS) Dinas Kesehatan Kota Surakarta - Mardanik, Tri, Elida Soviana, S.Gz., M.gizi (2017)
Background : Blood pressure in the Civil Service should be controlled. Uncontrolled blood pressure will affect the body organs, leading to degenerative diseases. Civil servant of Surakarta City Health Office often consume fast food containing a lot of sodium, which can increase blood pressure. In addition potassium consumption also has an effect on blood pressure. Objective :To determine the association of sodium and potassium intake with blood pressure in Civil Servants (PNS) of Surakarta City Health Office. Methods : The study design was cross sectional. 39 civil servants in Surakarta City Health Office were recruited using simple random sampling method. Blood pressure was obtained using sphygmomanometer. Sodium and potassium intake were obtained by interview using 1 month Food Frequency Questionary (FFQ). Data were analyzed using Pearson Product Moment and Rank Spearman test. Result : 61,5% and 38,5% of the respondens have sodium intake of 80% - 100% and >100% of requirement, respectively. 94,9% and 5,1% of the respondens have pottasium intake of <80% and 80%-100% of requirement, respectively. 56,4%, 30,8%, and 12,8% of the respondens have systolic blood pressure of <120 mmHg, 120-139 mmHg and 140-159 mmHg, respectively. 48,7%, 41% and 10,3% of the respondens have diastolic blood pressure of <80 mmHg, 80-89 mmHg and 90-99 mmHg, respectively. Based on statistic analysis there is an association of sodium intake to systolic and diastolic blood pressure with p-value 0,001 and 0,040, respectively. No association of potassium intake to systolic and diastolic blood pressure with p- value 0,308 and 0,085, respectively. Conclusion : There is an association of sodium intake with blood pressure No association potassium intake on blood pressure. Keywords: Sodium intake, Potassium Intake, Blood Pressure.